Boosting one-step conversion of cyclohexane to adipic acid by NO2 and VPO composite catalysts. Issue 16 (29th January 2016) - Jian, Jian; You, Kuiyi; Duan, Xuezhi; Gao, Hongxu; Luo, Qing; Deng, Renjie; Liu, Pingle; Ai, Qiuhong; Luo, He'an
Abstract : A highly selective one-step synthesis of adipic acid from the catalytic oxidation of cyclohexane with NO2 . Abstract : We demonstrate VPO composites as efficient catalysts for highly selective oxidation of cyclohexane to adipic acid with NO2 . In particular, the Ni–Al–VPO composite catalyst exhibits the striking conversion of cyclohexane (60.6%) and exceptionally high selectivity towards adipic acid (85.0%). Moreover, N2 O is an environmentally harmful gas, and its yield in the present process is only 0.03 t/t adipic acid, which is far below that obtained using the industrial method (0.3 t/t adipic acid). This work provides a new strategy for the one-step synthesis of dicarboxylic acids from cycloalkanes.